PEMBELAJARAN MENULIS TEKS ULASAN BUKU NOVEL “LASKAR PELANGI” MENGGUNAKAN METODE MIND MAPPING PADA PESERTA DIDIK KELAS VIII MTSS SIRNAMISKIN BANDUNG - Zevanya Claudia Sitinjak; Dheni Harmaen; Adi Rustandi (STKIP Subang, 2022)
Indonesian Junior High School subjects in the 2013 Curriculum are already text-based, one of which is a review text that requires students to express factual ideas according to the object or work being reviewed. This study aims to determine the writer's ability to plan, implement, and evaluate learning to write review texts; knowing the ability of students in writing review texts; and knowing the level of effectiveness of using the Mind Mapping method in writing review texts. The type of research used is a quasi-experimental involving the experimental class and the control class. As for the results of this study, the researcher was able to plan learning to write novel book review texts. Researchers obtained planning scores with an average value of 3.56 in the experimental class and 3.56 in the control class, then in implementing and evaluating learning the researchers obtained an average value of 3.58 in the experimental class, and 3.52 in the control class. , so it is included in the very good category. The results of the pretest of the experimental class students obtained an average pretest score of 44, while the control class received an average score of 18. The posttest results of the experimental class students obtained an average score of 80, and the control class obtained an average score of 37. So that the average value of the pretest and posttest of the experimental class is better than the control class. The results of the effectiveness of the Mind Mapping method in the experimental class were carried out through the Gain test by obtaining a Mean value of 64. Meanwhile, the control class obtained an average value of Mean 22 with the discussion method. So the use of the Mind Mapping method is more effective than the discussion method.